Male Homosexuality in Brazilian Indexing Languages: Some Ethical Questions - Pinho, Fabio Assis; Guimarães, José Augusto Chaves [UNESP] (Ergon-verlag, 2012)
Studies on ethics in information organization have deeply contributed to the recognition of the social dimension of Information Science. The subject approach to information is linked to an ethical dimension because one of its major concerns is related to its reliability and usefulness in a specific discursive community or knowledge domain. In this direction, we propose, through an exploratory research design with qualitative and inductive characteristics, to identify the specific terminology that Brazilian indexing languages allow for terms relating to male homosexuality. We also analyzed the terms assigned to papers published in the Journal of Homosexuality, Sexualities and Journal of Gay & Lesbian Mental Health between the years 2005 to 2009. From this analysis of terms and the Brazilian indexing languages, we see (1) the Brazilian context, (2) imprecision in the terminology, (3) indications of prejudices disseminated by political correctness, (4) biased representation of the subject matter, (5) and the presence of figures of speech.